1988
DOI: 10.1002/art.1780310706
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipoproteinemia in pediatric systemic lupus erythematosus

Abstract: Patients with systemic lupus erythematosus are at increased risk for premature atherosclerosis. We examined one possible etiologic factor, dyslipoproteinemia, both before and after corticosteroid therapy. We identified 2 distinct patterns of dyslipoproteinemia. One is attributable to active disease; the other is attributable, in part, to corticosteroid therapy. The dyslipoproteinemia of active disease consists of depressed high density lipoprotein cholesterol and apoprotein A-I with elevated very low density l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
57
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(69 citation statements)
references
References 42 publications
10
57
1
1
Order By: Relevance
“…Similar to previous studies, we found that total cholesterol levels were frequently abnormal both at the time of diagnosis and over the course of the disease (25,41). The percentage of patients with abnormal levels was only slightly higher at time of presentation than at other times and remained relatively constant in subsequent years.…”
Section: Sarkissian Et Alsupporting
confidence: 90%
See 4 more Smart Citations
“…Similar to previous studies, we found that total cholesterol levels were frequently abnormal both at the time of diagnosis and over the course of the disease (25,41). The percentage of patients with abnormal levels was only slightly higher at time of presentation than at other times and remained relatively constant in subsequent years.…”
Section: Sarkissian Et Alsupporting
confidence: 90%
“…A previous study of 10 newly diagnosed pediatric patients with SLE described the active SLE pattern of increased levels of triglycerides and VLDL cholesterol with depressed levels of HDL cholesterol and apolipoprotein A-I. Following the initiation of steroid therapy, levels of total cholesterol, LDL cholesterol, and HDL cholesterol rose, with lesser increases in the levels of VLDL cholesterol and triglycerides (25). …”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations